Spatio-temporal variation of seed rain between urban and rural fragments of humid tropical forests - Santos, Priscila Silva dos; Andrade da Silva, Kleber; Araújo, Elcida de Lima; Santos, Danielle Melo dos; Santos, Josiene Maria Falcão Fraga dos; Prazeres, Gicélia Lira dos; Ferraz, Elba Maria Nogueira (Revista de Biología Tropical, 2023)
Introduction: The type of land use surrounding the remnants of tropical forest may generate changes in the characteristics of plant populations and communities. Consequently, there may be a significant reduction in processes of pollination and diasporas dispersion. Therefore, causing changes in some parameters of seed rain. Objective: To characterize and compare seed density, species richness, floristic composition, habit, dispersal syndrome, and successional category of seed rain between urban and rural fragments of Atlantic Forest, in the 2015 and 2016 weather seasons. Methods: The study areas were defined after mapping and quantification of urban and rural occupations around the remnants, based on satellite images. In each fragment, were installed 36 collectors of 0.25 m2. The material was collected monthly during two consecutive years. Results: Seed rain richness was higher in the urban fragment during the rainy season in the two years, whereas it was similar between the fragments in the dry season. The seed density in the rural fragment was higher than in the urban during the rainy season; did not vary in urban between years or between seasons; and it was higher in the rural fragment in the rainy season of one year. There was a difference in the floristic composition of the seed rain between the fragments along time. The variations in the functional attributes of habit, dispersal syndrome, and successional category, were explained by the variables fragment, season, and year. Conclusions: Differences in the characteristics of the seed rain between the fragments might reflect the spatial and temporal heterogeneity, due to the diverse uses of the soil and external pressures (anthropogenic actions) present in the surroundings of the forest fragments and temporal variation in precipitation.